Temperature response of soil carbon decomposition depends strongly on forest management practice and soil layer on the eastern Tibetan Plateau - Kaijun Yang; Ruoyang He; Wanqin Yang; Zhijie Li; Liyan Zhuang; Fuzhong Wu; Bo Tan; Yang Liu; Li Zhang; Lihua Tu; Zhenfeng Xu (Scientific Reports, 2017)
Abstract How forest management practice impacts the temperature response of soil carbon decomposition remains unclear in Tibetan boreal forests. Here, an experiment was conducted to compare soil carbon decomposition of two layers (organic and mineral) in three Tibetan forests (natural forest, NF; secondary forest, SF; spruce plantation, PF). Soils were incubated at two temperatures (10 °C and 20 °C) for 219 days. Increased temperature often stimulated carbon decomposition rates of organic layer but did not affect them in the mineral soils. Soil carbon decomposition rates in the organic layer followed a pattern of NF > SF > PF over the incubation period. Regardless of forest type, soil carbon decomposition rates and temperature coefficient (Q 10) were higher in the organic layers compared to mineral soils. Moreover, forest type conversion increased Q 10 values in each soil layer. Taken together, our results suggest that forest management practice has much stronger impacts on biochemical properties in the organic layers relative to mineral soils. Moreover, the temperature responses of soil carbon decomposition depend largely on forest management practice and soil layer in this specific area.